A Study of Tectonic Culture and Technology of Religious Masonry Architecture in Wuhan - Chen, Ru (ICONARCH International Congress of Architecture and Planning, 2014)
Western style masonry architecture had been much promoted because of western influences since the mid-nineteenth century, and the well preserved Griffith Church in Wuhan was a representative to investigate its tectonic culture and technology. While the various masonry methods applied in its brick wall, its door and window openings, and its main structure, were largely western in nature, the Chinese or the local methods were incorporated where appropriate. This shows that the tectonic culture and technology of contemporary religious masonry architecture in China could not be fully understand without a consideration of the Chinese architectural tradition and the social context. Also, with respect to construction technology and spatial expression, Griffith Church could provide invaluable lessons in the exploration of construction potential and architectural treatment of the brick masonry.